2009
DOI: 10.1007/s11745-009-3303-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Molecular Characterization of the Acyl‐CoA:Diacylglycerol Acyltransferase 1 (DGAT1) Gene from Echium

Abstract: Boraginaceae species, such as those from the genus Echium, contain high levels of the Delta(6)-desaturated gamma-linolenic (18:3n-6) and octadecatetraenoic (18:4n-3) acids. These are unusual fatty acids among the plant kingdom that are gaining interest due to their benefits to human health. The potential utility of acyltransferases aimed at an increase in oil yield and fatty acid profiling has been reported. In this work, a gene encoding an acyl-CoA:diacylglycerol acyltransferase (DGAT, EC 2.3.1.20) was cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 75 publications
4
21
0
Order By: Relevance
“…This hypothesis is supported by the fact that some unusual fatty acids are found in both polyesters and seed oils, and by the observation that several enzymes of unusual fatty acid synthesis are divergent forms of enzymes of normal fatty acid synthesis. A number of molecular studies on lipid biosynthesis have been performed in Echium plants (García-Maroto et al 2002;Mañas-Fernández et al 2009) which are characterized by the accumulation of unusual D 6 -desaturated fatty acids (c-linolenic and stearidonic acids) in the seed oil. Here, we report on the cloning and molecular characterization of EpGPAT1, a homolog of Arabidopsis polyestertype GPATs which was isolated from the seeds of Echium pitardii (Boraginaceae).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by the fact that some unusual fatty acids are found in both polyesters and seed oils, and by the observation that several enzymes of unusual fatty acid synthesis are divergent forms of enzymes of normal fatty acid synthesis. A number of molecular studies on lipid biosynthesis have been performed in Echium plants (García-Maroto et al 2002;Mañas-Fernández et al 2009) which are characterized by the accumulation of unusual D 6 -desaturated fatty acids (c-linolenic and stearidonic acids) in the seed oil. Here, we report on the cloning and molecular characterization of EpGPAT1, a homolog of Arabidopsis polyestertype GPATs which was isolated from the seeds of Echium pitardii (Boraginaceae).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from these three DGAT types, bifunctional wax ester synthases also can catalyze the DGAT reaction . Depending on the species, DGAT enzymes can have strong preferences for different acyl-CoA or DAG substrates Huang, 1986, 1987;Griffiths and Harwood, 1991;Mañas-Fernández et al, 2009;Furmanek et al, 2014).…”
mentioning
confidence: 99%
“…(ii) Hydrophobicity analysis showed that RdD-GAT had four transmembrane domains, which was very different from DGAT1 and DGAT3. Members of DGAT3 family are cytosolic enzymes which lack any transmembrane domains in the protein structure, while members of DGAT1 family were predicted to contain at least eight highly hydrophobic transmembrane regions (Guihéneuf et al 2011;Mañas-Fernández et al 2009 Fig. 2 Phylogenetic analysis of homolog sequences of RdD-GAT across the organisms.…”
Section: Discussionmentioning
confidence: 99%